105. Upgrading Philips Allura Xper FD20 angiography system to Allura Clarity: Analysis of dose reduction and image quality. (December 2018) - Taddeucci, A.; Piffer, S.; Redapi, L.
Abstract : Purpose: Our Allura Xper FD20 system was installed in 2013 and mainly used for stroke treatment. To reduce the radiation dose delivered to patients though maintaining the required image quality, the system was recently upgraded to Allura Clarity. The core characteristics of Allura Clarity family are new real-time image processing algorithms to reduce image noise. The aim of this work is to show the advantages obtained in terms of dose reduction for cardiac, vascular and electrophysiological studies following such upgrade. Methods: For both angiographic systems, the patient dose was assessed by means of K a, e (Entrance Air Kerma) measurements, using a PMMA phantom to simulate patient attenuation. The measurement set up was the referred method indicated in the RP162 report[1] and extensively described by Martin[2] . For each investigated procedure, the measurements were carried out for most selectable fields of view and different PMMA thicknesses. The image quality was evaluated using Leeds TOR 18FG and FluoroMesh phantom for low contrast resolution and spatial resolution respectively. Results: Depending on the procedure, the dose reduction is meaningful and ranges from 20% up to a factor of around 4 for fluorographic acquisitions. All K a, e values measured on Allura Clarity system are compliant with the Suspension Levels set out in the RP162 report[1] also for digital fluorographic acquisition mode. The image quality obtained with Allura Clarity is equivalent to that of the previous system. Conclusions: The Allura Clarity delivers much lower dose to the patient for all clinical applications while maintaining an equivalent image quality.